ANALISIS KEPUASAN PENGUNJUNG DAN POTENSI PENGEMBANGAN PADA OBJEK WISATA PANTAI MUTUN DI KABUPATEN PESAWARAN - Vela Trecylia; Firdasari .; Lina Marlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
This study aims to analyze the level of visitors’ satisfaction at Mutun Beach, the tourist attributes that need to be improved and maintained by Mutun Beach, and to find out the driving and inhibiting factors development of Mutun Beach. The method used in this research was a survey method. The samples in this study were 4 Mutun employees and 77 visitors, which were taken using purposive sampling and accidental sampling methods. Data collection was carried out in January - February 2023. The data analysis methods used were Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), and descriptive analysis. The results of this study indicated that the level of visitor satisfaction is in the "Satisfied" category with a CSI value of 74.77%. Based on the IPA method, tourism attributes that need to be improved are the condition of game facilities such as banana boats, rubber boats and water booms, the safety of water boom, and the condition of toilet and prayer room facilities. Tourism attributes that need to be maintained are the attractiveness of the beach, cleanliness, comfortable atmosphere, calm sea water, various and condition of infrastructure and game facilities, and good service. Factors that are driving the development of Mutun Beach are high tourist attractiveness, easy accessibility, complete facilities, good service and management, and government’s role. The inhibiting factors are limited promotion, competitors or other beaches around Mutun, and limited funds and human resources.Key words: CSI, development potential, IPA, visitor satisfaction